The association of left ventricular ejection fraction with incident heart failure in patients with atrial fibrillation. (3rd October 2022) - Hamatani, Y; Iguchi, M; Minami, K; Ishigami, K; Ikeda, S; Doi, K; Yoshizawa, T; Masunaga, N; Esato, M; Tsuji, H; Wada, H; Hasegawa, K; et al.
Abstract: Background: Atrial fibrillation (AF) increases the risk of incident heart failure (HF). Left ventricular ejection fraction (LVEF) is an important prognostic parameter in patients with HF. However, little is known regarding the association of LVEF with incident HF in patients with AF. Purpose: The aim of this study is to investigate the relationship between LVEF at enrollment and incidence of HF hospitalization during follow-up period in patients with AF. Methods: The Fushimi AF Registry is a community-based prospective survey of patients with AF in Fushimi-ku, Kyoto, Japan. The inclusion criterion of the registry is the documentation of AF at 12-lead electrocardiogram or Holter monitoring at any time, and there are no exclusion criteria. We started to enroll patients from March 2011, and follow-up data were available for 4, 489 patients by the end of August 2021. In the present study, we investigated 3, 544 patients with the data of LVEF at enrollment. We divided the patients into 4 groups stratified by LVEF (reduced LVEF [LVEF <40%], mildly reduced LVEF [LVEF: 40–49%], slightly reduced LVEF [LVEF: 50–59%], and normal LVEF [LVEF ≥60%]), and compared the backgrounds and outcomes between these 4 groups. Results: Of 3, 544 patients, the mean age was 73.6±10.7 years, 1, 420 (40%) were female, 1, 781 (50%) were paroxysmal AF, and 1, 085 (30%) had pre-existing HF. The mean CHADS2 and CHA2DS2-VASc scores were 2.1±1.3 and 3.4±1.7, respectively. The mean LVEF at enrollment was 63±12% (reduced LVEF: 197 [6%], mildly reduced LVEF: 250 [7%], slightly reduced LVEF: 532 [15%] and normal LVEF: 2, 565 [72%], respectively). Patients with lower LVEF demonstrated lower prevalence of female and paroxysmal AF, and had a higher CHADS2 and CHA2DS2-VASc scores (all P<0.01). A total of 605 patients were hospitalized for HF during the median follow-up period of 5.5 years, corresponding to an annual incidence of 3.4% per person-year. Kaplan-Meier curves demonstrated that LVEF at enrollment could stratify the incidence of HF hospitalization during follow-up in patients with AF (Picture 1). Multivariable Cox regression analysis revealed that lower LVEF strata were significantly associated with the increased risk of HF hospitalization even after adjustment by age, sex, type of AF and CHA2DS2-VASc score (Picture 1). An increased risk of HF hospitalization was observed even in patients with mildly reduced LVEF (adjusted hazard ratio: 2.56, 95% CI: 1.99–3.29) as well as in those with slightly reduced LVEF (adjusted hazard ratio: 1.79, 95% CI: 1.45–2.22) compared with those with normal LVEF. These results were also the case in AF patients without pre-existing HF (Picture 2). Conclusion: LVEF at enrollment could stratify the incidence of HF hospitalization in patients with AF, suggesting the importance of measuring LVEF in all patients with AF. Even mildly (LVEF: 40–49%) or slightly (LVEF: 50–59%) reduced LVEF was independently associated with the risk of incident HF in patients with AF. Funding Acknowledgement: Type of funding sources: None.